Rare Chinese Ceramic Imports of the Golden Horde Period from Bolgar - Igor V. Volkov; Airat M. Gubaidullin; Oxana V. Lopan (Археология евразийских степей)
This paper deals with rare groups of Chinese pottery imports from the excavations by A.M. Gubaidullin on the Bolgar fortified settlement. One of the rarest is a fragment of Jun ware. The growth of production in Henan province was during the Song Dynasty (960–1279), and after the Mongol conquest it has declined. In the Ulus of Jochi, such isolated finds are edentified exclusively in Bolgar. Since they are not found in the well-studied Golden Horde layers of the XIV century in all other sites, our objects should be attributed to the XIII century. A rare but steady import in the Golden Horde cities are Chinese pottery of the Cizhou ware: their fragments are represented on many large excavations in Bolgar and capitals. The Cizhou vessel, published here, belongs to wine vases and is decorated with a traditional painting for this group – with stylized chrysanthemums in the upper part and with the plot "phoenix in the clouds" in the main tier. The number of the finds of the Cizhou ware whole vessels in the Golden Horde cities is small, and our vessel is the most preserved and expressive in painting. It dated to the second half of the XIV century by the stratigraphy and also by the fragment of an octagonal Qinghua porcelain bottle with a blue-and-white painting, which was found together. The Golden Horde complexes can provide valuable reference dates to clarify the chronology of Chinese imports.